The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.24251/hicss.2021.696
|View full text |Cite
|
Sign up to set email alerts
|

Requirements Identification for Real-Time Anomaly Detection in Industrie 4.0 Machine Groups: A Structured Literature Review

Abstract: Industrie 4.0 environments generate an unprecedented amount of production data. This is due to the rising number of sensors and interconnected devices capable of emitting data in millisecond frequencies. Streaming analytics offers promising methodologies that can support handling and analysis of data volume and variety. Transparency and control over real-time data can increase production efficiency in tightly connected machine environments. Data transparency may avoid time-consuming assessment of machines to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Context-specificity results from mechanisms used to analyze and evaluate production data regarding adherence to expectation. In related studies, three categories for design principles are identified regarding real-time anomaly detection evaluation, namely timeliness, threshold setting and qualitative anomaly assessment as presented in the following [7,13,18].…”
Section: Evaluation Categories For Real-time Anomaly Detection In Industrie 40mentioning
confidence: 99%
See 4 more Smart Citations
“…Context-specificity results from mechanisms used to analyze and evaluate production data regarding adherence to expectation. In related studies, three categories for design principles are identified regarding real-time anomaly detection evaluation, namely timeliness, threshold setting and qualitative anomaly assessment as presented in the following [7,13,18].…”
Section: Evaluation Categories For Real-time Anomaly Detection In Industrie 40mentioning
confidence: 99%
“…According to [13], timeliness is of major importance as optimal algorithms are supposed to detect anomalies as early as possible, so that countermeasures against anomalies can be initiated as soon as possible. The structured literature review presented in [18] identifies requirements for real-time anomaly detection in Industrie 4.0. The majority of analytical requirements such as fast data preparation emphasizes the importance of timeliness.…”
Section: Evaluation Categories For Real-time Anomaly Detection In Industrie 40mentioning
confidence: 99%
See 3 more Smart Citations